Optical absorption and photoconductivity of ZnSe:Co single crystals - Vaksman, Yu.F.; Pavlov, V.V.; Nitsuk, Yu.A.; Purtov, Yu.N.; Nasibov, A.S.; Shapkin, P.V. (Functional Materials, 2007)
Influence of cobalt impurity on the optical absorption and photoconductivity spectra of zinc selenide crystals has been considered. Basing on optical and electophysical studies results, the scheme of electronic transition in the investigated crystals is presented.